Eco-agri-food systems: today's realities and tomorrow's challenges - Pengue, Walter Alberto (2018)
Provides an overview of the diversity of agriculture and food systems, each with different contributions to global food security, impacts on the natural resource base and ways of working through food system supply chains. We describe “eco-agri-food systems” and further identify their many manifestations through a review of typologies. We identify challenges ahead with existing systems due to prevailing economic and political pressures resulting in patterns of invisible flows and impacts across global food systems. We describe pathways to ensure sustainability by securing the benefits from working with, rather than against, natural systems and ecosystem processes and the challenges for farmers, communities and societies to reorient food value chains and build resilience in eco-agri-food systems